1998
DOI: 10.1590/s0102-76381998000400004
|View full text |Cite
|
Sign up to set email alerts
|

Miniesternotomia para a cirurgia da valva aórtica: experiência inicial

Abstract: É apresentada a experiência inicial com a cirurgia minimamente invasiva para o tratamento das afecções da valva aórtica, através da miniesternotomia em L invertido. No período de junho a novembro de 1997, 12 pacientes adultos foram submetidos a troca da valva aórtica. A técnica cirúrgica constitui-se na substituição da valva aórtica por prótese biológica, através de minitoracotomia, com esternotomia parcial do tipo L invertido, estendendo-se da fúrcula ao quarto espaço intercostal direito. O reduzido trauma ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We do not consider it necessary to extend the incision as far as the 4 th intercostal space 5 , because the 3 rd intercostal space provides enough room for the creation of the pouch in the right atrial auricle, as well as for drainage of the left chambers through a catheter introduced into the superior pulmonary vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not consider it necessary to extend the incision as far as the 4 th intercostal space 5 , because the 3 rd intercostal space provides enough room for the creation of the pouch in the right atrial auricle, as well as for drainage of the left chambers through a catheter introduced into the superior pulmonary vein.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this problem, Steven Gundry, from Loma Linda, proposed access through mini-sternotomy, with an incision extending from the manubrium of the sternum to the 3 rd intercostal space, where the incision is deviated to the right, like an inverted L, preserving the right internal thoracic artery 4 . Dias et al 5 reported an initial experience with mini-sternotomy, extending the incision to the 4 th intercostal space. All these controversial approaches resulted in a panel discussion 6 in which Steven Gundry enthusiastically supported this access approach.…”
mentioning
confidence: 99%
“…They considered this approach advantageous allowing utilization of the regular equipment used in traditional surgeries as it does not need cannulation of the femoral veins, as well as enabling the rapid conversion to total sternotomy. Since then, this access has been widely used in different institutions [3,[8][9][10].…”
Section: Commentsmentioning
confidence: 99%